Visual task enhances spatial selectivity in the human auditory cortex - Salminen, Nelli; Aho, Joanna; Sams, Mikko (Frontiers in Neuroscience, 2013)
The auditory cortex represents spatial locations differently from other sensory modalities. While visual and tactile cortices utilize topographical space maps, for audition no such cortical map has been found. Instead, auditory cortical neurons have wide spatial receptive fields and together they form a population rate code of sound source location. Recent studies have shown that this code is modulated by task conditions so that during auditory tasks it provides better selectivity to sound source location than during idle listening. The goal of this study was to establish whether the neural representation of auditory space can also be influenced by task conditions involving other sensory modalities than hearing. Therefore, we conducted magnetoencephalography (MEG) recordings in which auditory spatial selectivity of the human cortex was probed with an adaptation paradigm while subjects performed a visual task. Engaging in the task led to an increase in neural selectivity to sound source location compared to when no task was performed. This suggests that an enhancement in the population rate code of auditory space took place during task performance. This enhancement in auditory spatial selectivity was independent of the direction of visual orientation. Together with previous studies, these findings suggest that performing any demanding task, even one in which sounds and their source locations are irrelevant, can lead to enhancements in the neural representation of auditory space. Such mechanisms may have great survival value as sounds are capable of producing location information on potentially relevant events in all directions and over long distances.